Bioactive compounds of the lipid fractions of agro-industrial waste - Silva, Ana Carolina da [UNESP]; Jorge, Neuza [UNESP] (Elsevier, 2014)
This study aimed at evaluating the oils extracted from seeds originating from agro-industrial waste, in order to identify the presence of bioactive compounds. Therefore, determinations of fatty acid profile, triacylglycerols, tocopherol composition, phytosterols, phenolic compounds, total carotenoids, and antioxidant capacity were performed in the oils of grape, guava, melon, passion fruit, pumpkin, soursop, and tomato seeds. Antioxidant capacity analysis was performed by the methods DPPH• , ABTS•+, FRAP, and β-carotene/linoleic acid, besides measure of oxidative stability in the oils. The oils showed to be predominantly unsaturated with high percentage of linoleic essential fatty acid (38.8 to 79.4%), besides presenting significant quantities of tocopherols, phytosterols, and phenolic compounds. Tomato and guava oils showed better results in the antioxidant capacity tests and pumpkin oil had higher induction period in the oxidative stability test (65.3 h). The results obtained in this study collect information that enables the use of new alternative sources of vegetable oils, obtained from agroindustrial waste, which may serve as raw material for food, chemical, and pharmaceutical industries.
Keywords: Waste; Seeds; Fruits; Vegetable oils; Bioactive compounds; Antioxidant capacity